Integration of Multi-Gender Roles in Women Farming Groups: Public Administration Policy Analysis in Bener Meriah Regency - Mursyidin, Mursyidin; Hafni, Nur; Darmansyah, Dedy; Mardhiah, Ainol; Zulkarnaen, Teuku; Yulianda, Riki; Rizki, Muhammad; Saputra, Jumadil (Universitas Teuku Umar, 2025)
This study aims to examine the dynamics of multi-gender roles within the Karya Maju Women Farmers Group (KWT) in Bener Meriah Regency, particularly with the management of Gayo coffee cultivation. Despite KWT being administratively overseen by women, this research identified that men's contributions remain substantial in facilitating physical labor, including land cultivation and the transportation of agricultural goods. This study employs a qualitative methodology utilizing in-depth interviews and participant observation to analyze patterns of gender involvement in KWT. The research findings indicate that while men's participation is not formally organized within the KWT framework, their presence illustrates the interdependence between women's managerial positions and men's physical labor. The incorporation of gender roles in KWT could enhance the efficiency and sustainability of agricultural enterprises, although it has not been adequately addressed in current regulations. This research concludes that KWT Karya Maju serves as a forum for women's empowerment and a platform for collaboration between women and men to enhance the welfare of agricultural families. This research advocates for the implementation of more inclusive and adaptable policies to address gender roles in the agricultural sector, hence enhancing organizational effectiveness and the sustainability of coffee production.